Supporting pregnant women not ready to quit smoking: an economic evaluation - Tuba Saygın Avşar; Louise Jackson; Pelham Barton; Matthew Jones; Hugh McLeod (BMC, 2022)
Abstract Objectives Some pregnant women are not ready or do not want to quit smoking completely, and currently there is no support provided for these women in the UK. Offering help to reduce smoking could reduce the health risks associated with smoking and increase the limited reach of the NHS Stop Smoking Services (SSS) for pregnant women. This study aimed to design and evaluate a hypothetical intervention aimed at pregnant women who are not yet ready or do not want to quit smoking entirely. Methods A hypothetical intervention, the Reduced Smoking During Pregnancy (RSDP) intervention, was conceptualised based on the best available evidence. The intervention was evaluated, using a decision-analytic model developed for SDP interventions. Two different scenarios, a base-case and a cautious-case were developed, and a cost-utility analysis and return on investment analysis were conducted. The uncertainty around the estimates was assessed, using deterministic and probabilistic sensitivity analyses. Results The RSDP intervention could prevent the loss of 13 foetuses and generate 43 quitters 1 year after delivery per 1000 women. In the lifetime analysis, the intervention was cost-effective in both scenarios, with an incremental cost of £363 (95% CI £29 to £672) and 0.44 (95% CI 0.32 to 0.53) QALYs gained in the base-case. Conclusions The study found that the hypothetical reduction intervention would produce significant health benefits, reduce smoking and be cost-effective. Offering pregnant smokers help to reduce smoking could reduce health inequalities, widen the reach of SSS and improve health. This economic evaluation of a novel, intensive intervention could inform the piloting of such interventions.